An antiaging skin care system containing alpha hydroxy acids and vitamins improves the biomechanical parameters of facial skin - Tran D; Townley JP; Barnes TM; Greive KA (Dove Medical Press, 2014)
Diana Tran, Joshua P Townley, Tanya M Barnes, Kerryn A Greive Ego Pharmaceuticals, Braeside, Victoria, Australia Background: The demand for antiaging products has dramatically increased in recent years, driven by an aging population seeking to maintain the appearance of youth. This study investigates the effects of an antiaging skin care system containing alpha hydroxy acids (AHAs) in conjunction with vitamins B3, C, and E on the biomechanical parameters of facial skin. Methods: Fifty two volunteers followed an antiaging skin care regimen comprising of cleanser, eye cream, day moisturizer, and night moisturizer for 21 days. Wrinkle depth (Ry) and skin roughness (Ra) were measured by skin surface profilometry of the crow's feet area, and skin elasticity parameters R2 (gross elasticity), R5 (net elasticity), R6 (viscoelastic portion), and R7 (recovery after deformation) were determined for facial skin by cutometer, preapplication and after 7, 14, and 21 days. Volunteers also completed a self-assessment questionnaire. Results: Compared to baseline, Ry and Ra significantly improved by 32.5% (P<0.0001) and 42.9% (P<0.0001), respectively, after 21 days of antiaging skin care treatment. These results were observed by the volunteers with 9 out of 10 discerning an improvement in skin texture and smoothness. Compared to baseline, R2 and R5 significantly increased by 15.2% (P<0.0001) and 12.5% (P=0.0449), respectively, while R6 significantly decreased by 17.7% (P<0.0001) after 21 days. R7 increased by 9.7% after 21 days compared to baseline but this was not significant over this time period. Conclusion: An antiaging skin care system containing AHAs and vitamins significantly improves the biomechanical parameters of the skin including wrinkles and skin texture, as well as elasticity without significant adverse effects. Keywords: alpha hydroxy acids, antiaging, nicotinamide, vitamin C, vitamin E, profilometry, cutometer